Impact of dry heat sterilization on the mechanical and functional performance of 3D printed medical devices for image-guided intervention - Mary Chase Sheehan; Sarah Kim; Sunandita Sarker; Govindarajan Srimathveeravalli (Annals of 3D Printed Medicine)
Polymer additive manufacturing (AM) is a powerful method for medical device prototyping, producing low-cost medical devices for resource limited settings and patient-specific customization. Plastic medical devices created with AM must undergo sterilization prior to in vivo experiments or use with patients. While prior studies have verified the feasibility and safety of sterilization of such devices, the impact on mechanical performance has not been studied. Temperatures during autoclave sterilization, a commonly used and widely available method, can match or exceed the melt temperature of Nylon-12 used for selective laser sintering. Here we tested the impact of single or multiple cycles of autoclave sterilization on the mechanical and functional performance of plastic components used with interventional radiology related medical devices (catheter hub, ablation probe handle, and implantable port). We found that up to 2 cycles of sterilization did not tangibly impact the manufacturability, function or surface finish of these devices. However, we found that more than one cycle of sterilization can compromise the mechanical strength of the devices, with geometric-linked variations in the level of change in stiffness (ranging from 12 – 23 %). In conclusion, autoclave sterilization is safe for single use AM medical devices, where repetition of the sterilization for device reuse can compromise mechanical performance.